Self-Sacrificing Parenting and The Effects on Children – A Socio Pedagogical Analysis - Rozaliya Kuzmanova-Kartalova (Педагогически форум)
The article offers an analysis of a not very commented and studied problem in Bulgaria related to the parental self-sacrifice and its consequences for children. The characteristic types of parental models with a tendency to self-sacrifice are studied and the main reasons for the realization of self-sacrificial parenting are discussed. Psycho-emotional and behavioral profile, opportunities for social expression and personal perspective of children with self-sacrificing parents are presented. The gaps in the process of children's development and the deficits formed as a result of this parental model are commented. Some approaches to working on the problem through prevention and specialized intervention for socio-pedagogical work with children and families with self-sacrificing parents are outlined.